Asparagine endopeptidase prompts breast cancer–related pericardial calcification by regulating IGF2 and integrin αvβ5 - Xuefeng Wang; Jian Sun; Bin Lan; Chunyu Wang; Jiayi Ma; Qiaoting Hu; Jun Liu; Haili Cheng; Hong Wen; Jieyu Lin; Xinyi Ren; Huabin Yu; et al. (Proceedings of the National Academy of Sciences, 2025)
Cardiac calcification, often seen in age-related diseases, impairs heart function, yet its association with malignant tumors remains largely overlooked. Our study revealed that pericardial calcification (PC) occurs in up to 80% of breast cancer patients with pulmonary metastasis. We demonstrate a reciprocal relationship where breast cancer drives PC, which in turn accelerates cancer progression in humans and mice. Lung metastases increase monocyte-derived macrophage and mesenchymal stem cell (MSC)-derived osteoblast infiltration in the pericardial tissue, triggering inflammation and calcification. Mechanistically, metastatic cancer cells in the lungs highly express and secrete asparagine endopeptidase (AEP), which cleaves IGF2BP3 to free IGF2. AEP and IGF2 contribute to PC by promoting osteoblast differentiation in heart tissue through integrin αvβ5 and IGF1R activation, respectively. Pharmacological blockade of integrin αvβ5 and IGF1R, especially when combined, effectively inhibits ectopic osteogenesis and disrupts the feedback loop between PC and cancer progression. These findings elucidate the interplay between metastatic breast cancer and PC and suggest therapeutic strategies to hinder breast cancer progression.